The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-2222.2008.03178.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the immunoglobulin classic antigen‐binding site regulates allergic airway inflammation in a murine model of experimental asthma

Abstract: Background When bound to mast cell FcεRI, IgE serves as antigen receptor for allergic reactions, permitting specific identification of the allergen. Although the core of the classic antigen-binding site is heavy chain complementarity determining region 3 (CDR-H3), recent studies suggest that allergens might also bind IgE in a superantigen-like fashion outside the classic antigen-binding site. Objective We sought to evaluate the contribution of the classic CDR-H3-centric antigen-binding site to the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Using a gene targeted mouse strain with a limited CDR-H3 repertoire, we revealed that allergic sensitization and airway inflammation highly depend on the predominant BCR repertoire (11). Therefore, we now sought to systematically characterize the composition of the murine IgE repertoire.…”
mentioning
confidence: 99%
“…Using a gene targeted mouse strain with a limited CDR-H3 repertoire, we revealed that allergic sensitization and airway inflammation highly depend on the predominant BCR repertoire (11). Therefore, we now sought to systematically characterize the composition of the murine IgE repertoire.…”
mentioning
confidence: 99%
“…A lthough several studies have addressed the characterization of the IgE repertoire (1), it is subject to ongoing discussion whether the IgE production in allergic disorders is due to an oligoclonally expanded B cell response (2). This is particularly interesting in the context of allergen-specific immunotherapy and the emerging anti-IgE therapy, which has redirected the spotlight in allergy treatment to the B cell (1).…”
mentioning
confidence: 99%
“…For nonsensitized controls, the dilutions were 1:10 (IgG 1 ) or 1:2 (IgE). OVA-specific IgE antibody levels were determined as previously described [10]. As standard, we used an OVA-specific murine IgE (Serotec, Oxford, UK).…”
Section: Animals and Methodsmentioning
confidence: 99%
“…IgE heavy chain transcripts were amplified and cloned as described previously [10]. Sequences were aligned with the ImMunoGeneTics (IMGT) VQUEST program (http://imgt.cines.fr) [17].…”
Section: Animals and Methodsmentioning
confidence: 99%
See 1 more Smart Citation